Diversity of Azotobacter in relation to soil environment in Ebinur Lake wetland - Zhong Zhengtao; Hu Wenge; Yang Di; He Yuan; Zhou Tingting (Biotechnology & Biotechnological Equipment, 2019)
Ebinur Lake wetland is the most representative temperate arid zone wetland ecosystem in China and it is the centre of the oasis and desertification of the Northern slope of Tianshan conjugate. Soil samples were collected from three sites (Tamarix ramosissima, Halocnemum strobilaceum, and Phragmites australis) and different soil layers (0–5, 5–15,15–25, and 25–35 cm) within this wetland during spring, summer and autumn, and the diversity of cultured/uncultured Azotobacter based on the 16S rDNA and nifH genes was characterized. Polymerase chain reaction denaturing gradient gel electrophoresis (PCR-DGGE) and bivariate correlation analysis were used to evaluate the relationship between the diversity of uncultured Azotobacter and soil environmental factors. A total of 17 cultured Azotobacter strains were isolated, five of which had stronger nitrogen-fixation ability (more than 10 mg/mL). Meanwhile, most of the cultured Azotobacter strain sequences were grouped into Bacillus sphaericus and Bacillus subtilis, and fewer sequences were affiliated with Actinomycetes. Furthermore, PCR-DGGE indicated that the diversity of uncultured Azotobacter was not balanced in some samples and the Shannon diversity index varied from 0.685 to 2.626. The uncultured Azotobacter were grouped into autotrophic genera Azotobacter and Rhizobium. Finally, bivariate correlation analysis showed that the diversity of uncultured Azotobacter was significantly correlated with soil organic carbon, inorganic carbon, NH4+-N, NO3−-N and microbial biomass N in the Ebinur Lake wetland in Xinjiang.